Adipose tissue angiogenesis in obesity - Lemoine, Amal Y.; Ledoux, Séverine; Larger, Etienne (Thrombosis and Haemostasis, 2013)
Adipose tissue is the most plastic tissue in all multicellular organisms, being constantly remodelled along with weight gain and weight loss. Expansion of adipose tissue must be accompanied by that of its vascularisation, through processes of angiogenesis, whereas weight loss is associated with the regression of blood vessels. Adipose tissue is thus among the tissues that have the highest angiogenic capacities. These changes of the vascular bed occur through close interactions of adipocytes with blood vessels, and involve several angiogenic factors. This review presents studies that are the basis of our understanding of the regulation of adipose tissue angiogenesis. The growth factors that are involved in the processes of angiogenesis and vascular regression are discussed with a focus on their potential modulation for the treatment of obesity. The hypothesis that inflammation of adipose tissue and insulin resistance could be related to altered angiogenesis in adipose tissue is presented, as well as the beneficial or deleterious effect of inhibition of adipose tissue angiogenesis on metabolic diseases.
Keywords: Angiogenesis and inhibitors; obesity; metabolic disorders